Human resource disclosure and practices : effects on firm financial performance and value - Norhayati Abdullah
The digital era has augmented the importance of non-financial information, specifically Human Resource Disclosure (HRD) in annual reports. Moreover, in line with the global recognition of human capital (HC) as a valuable intangible resource, it is essential that HR practices (HRP) of public listed companies be addresed through HRD to ensure that this value is captured by the market. Accordingly, the main objective of this study is to investigate the quality of HRD in Malaysia from 2010 to 2014. Next, the quality of HRD in the annual reports of 2016 was compared against the actual HRP in these companies. Additionally, this study tested the association between HRD against HRP as well as HRP with financial performance. The study also examined the value relevance of both HRP and HRD on firm value. Finally, this study analysed the mediation effect of HRD and firms' financial performance on the association between HRP and firm value. In order to meet these research objectives, both secondary and primary data were obtained through two methods: content analysis of annual reports and a questionnaire survey. Specifically, the analysis on the trend of quality of HRD was based on 1,175 firm-year' data. The measures of association between HRP, HRD, financial performance and firm value were based on data from 93 companies. This research employed lnstitutional Theory, Resource Based View Theory (RBV) and semi-strong form of Efficient Market Hypothesis (EMH) to develop the hypotheses. Overall, the findings reveal that there is an increasing trend of HRD quality from 2010 to 2014. However the significant increase is only between 2012 and 2013. lnterestingly, companies are underreporting their HRD in their annual reports, despite it positive association with HRP. Nevertheless, quality of HRD, as well as HRP, have significant positive effects on firm value. However, the association between HRP and firms' financial performance is not statistically significant in this study. Additionally, HRD mediate the association between HRP and firm value, but not financial performance. This study provides empirical support for Institutional theory's coercive isomorphism, through its findings on quality of HRD. More importantly, the finding from HRP on firm value is in line with RBV theory, as HR and HC are considered resources to the companies. Finally, the mediating role of HRD in HRP and firm value relation hip is consistent with the semi-strong form of EMH. The findings of this study are useful to regulators and the companies as it reveals that although regulation has resulted in an increase in quality of HRD, considerable improvement is still needed. HRD should be communicated in companies' annual reports, because this information has been found to be value relevant to market participants. Nevertheless, it should be reassuring for stakeholders to know that despite the low level of HRD quality discovered in Malaysian companies, most of these companies have implemented effective HRP.